Deriving duties: Fichte's alternative to Kant - Rohlf Michael (Belgrade Philosophical Annual)
In this paper, I interpret and evaluate Fichte's criticisms of Kant's methods of deriving and systematizing ethical duties in The System of Ethics (1798), as well as the alternatives that Fichte proposes to Kant's methods. In short, Kant derives ethical duties using his Formulas of Universal Law (FUL) and Humanity (FH), and he systematizes the resulting duties into four classes structured by the distinctions between duties to oneself and to others, on the one hand, and perfect and imperfect duties, on the other hand. Fichte, however, accepts FH as a principle for specifying some duties to others but denies that FH captures our duties to or toward ourselves, and he rejects FUL as a positive criterion of duty altogether. In place of Kant's methods, Fichte derives ethical duties through reflection on the conditions of being a self and a moral agent, where these conditions include continuous, reciprocal, and formally free interaction between one's intellect and body, the sensible world, and other rational beings; and he replaces Kant's system of classifying duties with two new distinctions between conditioned and unconditioned duties, on the one hand, and universal and particular duties, on the other. I argue that Fichte's alternative to Kant's approach to deriving and systematizing duties results in a more intuitive and streamlined way of specifying many of the same duties that Kant recognized, and that Fichte's departures from Kant are well-motivated from within Kant's own framework.